Lipid metabolism in ruminant animals - Christie, William W. (Pergamon Press, 1981)
Lipid Metabolism in Ruminant Animals is a nine-chapter book that first discusses the anatomy, physiology, and microbiology of the ruminant digestive tract. Subsequent chapters center on lipid metabolism in the rumen; digestion, absorption and transport of lipids in ruminant animals; the composition, structure and function of lipids in the tissues of ruminant animals; and the effects of diet and other factors on the lipid composition of ruminant tissues and milk. Other chapters focus on lipid metabolism in the mammary gland, adipose tissue, liver, and other selected tissues of ruminant animals.